Push-Pull Aircrafts - Cohn, Miriam, author 646495 (Delhi, India : Orange Apple : World Technologies, 2012)
The Adam A500 is a six-seat civil utility aircraft that was produced by Adam Aircraft Industries. The aircraft is of pod-and-boom, push-pull configuration with its two Continental TSIO-550-E piston engines mounted to provide centerline thrust. Adam Aircraft ceased operations on 11 February 2008, and filed for Chapter 7 bankruptcy on 19 February 2008, having delivered seven A500s. In April 2008 Adam Aircraft was purchased from bankruptcy by AAI Acquisition Inc. the time of purchase this new company indicated that they would pursue certification 0 the A700 jet as a priority and that the A500 would not be produced due to the continuing poor market for piston -engined aircraft. AAI went out of business in April 2009 without producing any aircraft. In July 2009 there was an indication that a new buyer, Triton America and Thomas Hsueh were interested in purchasing the A500 design and returning the aircraft to production. The A500 was developed from the M-309 CarbonAero technology demonstrator designed by Burt Rutan and built by Scaled Composites at the Mojave Airport. The 309 designation refers to this being Rutan's 309th aircraft design . The 309 first flew in Marc 2000 , but the aircraft has since been gutted and was used as a static display outside the Adam Aircraft Industries headquarters . In 2006 the 309 was loaned to the Wings Over the Rockies Air and Space Museum and is now on display outside.